Hamiltonian and Lagrangian BRST Quantization in Riemann Manifold II - Pandey, Vipul Kumar (Advances in High Energy Physics, 2022)
We have previously developed the BRST quantization on the hypersurface VN−1 embedded in N-dimensional Euclidean space RN in both Hamiltonian and Lagrangian formulation. We generalize the formalism in the case of L-dimensional manifold VL embedded in RN with 1≤L<N. The result is essentially the same as the previous one. We have also verified the results obtained here using a simple example of particle motion on a torus knot.